IN-SITU STRESS MEASUREMENT BY OVERCORING AND HYDRAULIC FRACTURING OF PAHANG-SELANGOR RAW WATER TRANSFER PROJECT (Jurnal Teknologi (Sciences & Engineering), 2016)
Estimation of in-situ stress orientation and magnitude is necessary for assessing the excavation risks for Pahang-Selangor Raw Water Transfer (PSRWT) tunnel project. However, the in-situ stress state of the rock generally differs according to area and depth. Therefore, the in-situ stress measurements test in the tunnel are determined in three (3) locations, which are at Adit 2, TBM 2, and Adit 3, in which the overburdens are 227, 1130, and 570 m, respectively. The stress relief method of overcoring technique and hydraulic fracturing by high stiffness system were applied for this project. The results demonstrate that the existence of high vertical stress was estimated in particular in the TBM 2. The maximum principal stress is determined nearly along the vertical direction. Meanwhile, the stress in the horizontal plane is relatively small, and the horizontal to vertical stress ratio is less than one (1). The direction of the horizontal stress obtained is N8E, N14W, and N41E. Results indicate that this method is suitable for estimating in-situ stresses in deep tunnels. The above data and their interpretations enhance the stress database for Peninsular Malaysia